Identified particles in quark and gluon jets - Abreu, P; Adam, W; Adye, T; Ajinenko, I; Alekseev, G; Alemany, R; Allport, P; Almehed, S; Amaldi, U; Amato, S; Andreazza, A; Andrieux, M; et al. (1997)
A sample of about 1.4 million hadronic Z decays, selected among the data recorded by the DELPHI detector at LEP during 1994, was used to measure for the first time the momentum spectra of K+, K0, p, Λ and their antiparticles in gluon and quark jets. As observed for inclusive charged particles, the production spectra of identified particles were found to be softer in gluon jets than in quark jets, with a higher total multiplicity. © 1997 Published by Elsevier Science B.V.